A new tree frog of the genus Rhacophorus (Anura: Rhacophoridae) from southern Vietnam - Rowley, Jodi J. L.; Thuy, Le Thi; Tran, Duong; Dao, Thi Anh; Stuart, Bryan L.; Huy, Hoang Duc (Zootaxa, 2010)
We describe a new species of rhacophorid frog from the Langbian Plateau in southern Vietnam. Rhacophorus vampyrus sp. nov. is distinguished from its congeners by a combination of: a pale tan to brick red dorsum; white throat, chest and belly; black flanks and anterior and posterior surface of thighs; grey to black webbing between fingers and toes; reduced finger webbing; and pointed projection at tibiotarsal articulation. At present, the new species is known from montane evergreen forest between 1470–2004 m elevation. Rhacophorus vampyrus sp. nov. is a phytotelm breeder, depositing eggs in foam nests in small tree-holes.